A Proposed Guideline with Building Information Modelling (BIM) for Virtual Transformation of Traditional Housing to Green Housing - Chen Kim Lim; Kian Lam Tan; Nguarije Hambira (International Journal of Supply Chain Management, 2018)
Generally speaking, in search of alternative ways that is meant to prevent environment pollution and its sub hazard consequences, developers and planners as well as the masses nowadays are encouraged to use what is call a green home when building their houses. These types of houses typically use resources that are environmentally responsive. However, this new approach to house developments lacks clearly defined and globally accepted standards on what constitutes a green model. Thus, this research aims to educate the public about sustainable transformations from traditional homes to green homes by modelling the 3D model virtually to illustrate the differences between the conventional homes and green homes and its impact on the environment, and demonstrate the types of green alternatives available in Malaysia in order to construct the green homes. The ultimate goal is to create digitally a 3D model of the green homes through Building Information Modelling (BIM). BIM allows the public to run computer simulations that help to understand and visualise the evolutions of the traditional homes to green homes. The digital 3D model is effective in influencing and educating the residents about the benefits of green housing practices and ways to incorporate green building technologies.